Membangun Keunggulan Kompetitif: Studi Pengaruh Ekosistem Kerja dan Motivasi Terhadap Kinerja Pegadaian Parepare - Rice, Veronica; Nur, Irawati; Natsir, Ulfa; Tijjang, Bakhtiar; Ali, Syahban Mada (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The purpose of this study is to determine the Work Environment and Work Motivation have a partial effect on the Performance of PT. Pegadaian (Persero) Parepare Branch. To find out the Work Environment and Work Motivation simultaneously affect the Performance of PT. Pegadaian (Persero) Parepare Branch. This research was conducted using Quantitative Method. The data analysis technique used is Multiple Linear Regression Analysis and uses the program SPSS for windows 26. The data used in this study used primary data sourced from the results of questionnaire that had been filled out by respondents. The findings of this study show that the work environment partially has a significant effect on employee performance at the PT. Pegadaian (Persero) Parepare Branch with a calculated value of 2,265 > t table 2,032 with a significant of 0.030 < 0.05 and partial work motivation has a significant effect on the performance of PT. Pegadaian (Persero) Parepare Branch with a calculated value of 7,266 > t table 2,032 with a significant value of 0.000 < 0.05 and simultaneously influential with Fcalculate values of 45,833 > 3.28 t tables with significant values of 0.000 < 0.05.